GsMTx4-blocked PIEZO1 channel promotes myogenic differentiation and alleviates myofiber damage in Duchenne muscular dystrophy - Wengang Wang; Mingyang Huang; Xiusheng Huang; Ke Ma; Ming Luo; Ningning Yang (Skeletal Muscle)
Abstract Background Duchenne muscular dystrophy (DMD) is a debilitating disease characterized by progressive muscle-wasting and a lack of effective therapy. Although the application of GsMTx4 has been shown to reduce muscle mass loss in dystrophic mice, the mechanism of action remains unclear. Methods We employed single-nucleus RNA sequencing data to scrutinize the expression of mechanosensitive channels in skeletal muscle. The upregulation of PIEZO1 and its precise localization were corroborated in DMD patients, mdx mice, and activated satellite cells. To delve into the role of the GsMTx4-blocked PIEZO1 channel in the myogenic program, we conducted comprehensive in vitro and in vivo studies encompassing the proliferation of satellite cells, differentiation of myoblasts, and calcium influx into myofibers. Utilizing both a PIEZO1 channel inhibitor, GsMTx4, and a PIEZO1 channel agonist, Yoda1, we explored the PIEZO1 channel’s impact on satellite cell proliferation and myogenic differentiation. Additionally, we explored the protective effect of the PIEZO1 channel on myofiber calcium influx using mdx mouse models and isolated single myofibers. Results PIEZO1 was upregulated in the muscle of DMD patients and was predominantly expressed in satellite cells and upregulated during satellite cell proliferation. Treatment with GsMTx4 increased the cross-sectional areas of myofibers and reduced the proportion of centrally nucleated fibers in mdx mice. GsMTx4 inhibited satellite cell proliferation while promoting myogenic differentiation. During myogenic differentiation, the YAP nuclear-cytoplasmic ratio increased in cells treated with GsMTx4 and showed a significant correlation with the nuclear localization of MyoG. In myofibers, GsMTx4 significantly reduced the level of p-CaMKII/CaMKII in muscle and calcium load. Conclusions PIEZO1 upregulation in DMD could potentially stem from an elevated proportion of proliferating satellite cells triggered by sarcolemma damage and muscle necrosis. The inhibition of the PIEZO1 channel by GsMTx4 plays a beneficial role in fostering myogenic differentiation and mitigating myofiber damage. The PIEZO1 channel emerges as a promising therapeutic target for addressing DMD.